Colitis: an unusual presentation of Wegener's granulomatosis. (21st February 2013) - Sinnott, Joseph Dalby; Matthews, Paul; Fletcher, Simon
Abstract : Wegener's granulomatosis (WG) also known as granulomatosis with polyangiitis (GPA) is an anti-neutrophil cytoplasmic antibody-positive (ANCA) vasculitis which most commonly affects the upper respiratory tract, lungs and kidneys. It is uncommon for colitis to be the primary reason for the first hospital admission related to WG. This case represents one of the few in the literature where colitis is associated with WG and in particular, where colonic involvement was the presenting symptom. The patient presented to hospital with a 3-day history of bloody diarrhoea and was treated for colitis. The disease progressed and during the second admission renal and pulmonary involvement was found. A renal biopsy showed a crescentic change and a CT-confirmed inflammatory changes in the caecum and ascending colon. A diagnosis of WG was made and appropriate treatment initiated. The patient is now in remission.